2018
DOI: 10.3892/ijmm.2018.3540
|View full text |Cite
|
Sign up to set email alerts
|

miR‑377 targets CUL4A and regulates metastatic capability in ovarian cancer

Abstract: Abstract. The incidence and recurrence rates of ovarian cancer are still high, and once the disease metastasizes, it is nearly always fatal. Cullin 4A (CUL4A) serves a significant role in tumourigenesis and tumour progression; however, the effect and mechanisms underlying cUL4A overexpression are still unknown. The role of microRNAs (miRs) in the regulation of metastatic capability in ovarian cancer cell lines was investigated. The interaction between miR-377 and cUL4A was investigated using bioinformatics ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Increasing evidence have elucidated that miRs are associated with inflammation in SS patients [9][10][11]. Besides, miR-377 has been found to mediate the proliferation and apoptosis progresses as well as DNA methylation in several malignancies [12][13][14]. Its modulatory functions on inflammation have been revealed in recent studies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence have elucidated that miRs are associated with inflammation in SS patients [9][10][11]. Besides, miR-377 has been found to mediate the proliferation and apoptosis progresses as well as DNA methylation in several malignancies [12][13][14]. Its modulatory functions on inflammation have been revealed in recent studies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence demonstrated abnormal expression of microRNAs were deeply associated with post-transcriptional regulations of target genes [21, 43, 44]. It had described high expression of miR-195-5p can down regulate human yep-associated protein (YAP) mRNA, so as to inhibit tumor development in cancers [45].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that miR-762 promoted EOC cell proliferation, migration, and invasion by upregulating Wnt/β-catenin signalling via suppression of menin [101], which has been reported to promote β-catenin cytoplasmic shuttling and degradation [129, 130]. Finally, miR-377, miR-101, miR-381, and miR-429 were found to target Cullin E3-Ring E3-ligase family member, CUL4A, membrane-associated E3 ubiquitin ligase MARCH7, transcription factor Ying Yang 1 (YY1), and the PNCA-associated factor, KIAA0101, respectively, in EOC [108, 114, 115, 117]. Ectopic expression of CUL4A, MARCH7, YY1, and KIAA0101 promoted β-catenin nuclear translocation and downstream target gene expression.…”
Section: Introductionmentioning
confidence: 99%